Eliminating the worst forms of child labour (2002)
This Handbook is intended to serve as a practical guide for parliamentarians in the fight against child labour. But there can be no doubt that it will also prove to be a valuable resource for many others who wish to see sustainable development and human rights enjoyed by all: governments,workers’ and employers’ organizations, civil society organizations, and anyone wishing to become involved in the govement to end the exploitation of children.